Pengujian Prototip Suspensi Aktif Tegar (Robust) Model Seperempat Kendaraan - Nyoman Bangsing (Institute for Research and Community Services (LPPM) ITB, 2004)
In this paper the result of the performance test of a robust-active suspension system will be presented. The performance of the developed suspension system was evaluated under a sinusoidal road disturbance with amplitude of 3 mm (peak to peak), and within the frequency test range of 1